Writing-Translating (from) the In-Between: An Interview with Gail Scott: An Interview with Gail Scott - Lane-Mercier, Gillian (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
While Gail Scott is well known in Canadian and American avant-garde literary circles as a writer of experimental novels, short stories, and essays, she is perhaps less well known as a literary translator of Québec fiction. Since 1998, Scott has published four literary translations of works by contemporary Québec authors whose writing reflects many of her own aesthetic concerns: Laurence by France Théoret (1998), The Sailor's Disquiet by Michael Delisle (2002), Helen with a Secret, also by Michael Delisle (2002), and Mile End by Lise Tremblay (2002). Although she has often addressed, in her essays and interviews, the importance of writing "in translation" when one lives at a linguistic and cultural crossroads, Scott has been less explicit about her work as a translator. This is the first interview in which she reflects on her conception of literary translation, as well as on the function, strategies, and liberties of the English language translator, notably in the context of Québec. She also considers the ways these issues at once "intersect" with and "intervene" in her writing, her role as public intellectual, and her world view.